Near-equatorial Pi2 and Pc3 waves observed by CHAMP and on SAMBA/MAGDAS stations. Issue 4 (15th February 2015) - Cuturrufo, F.; Pilipenko, V.; Heilig, B.; Stepanova, M.; Lühr, H.; Vega, P.; Yoshikawa, A.
Highlights CHAMP satellite and near-equatorial array SAMBA/MAGDAS observed simultaneous Pc3/Pi2 waves. Nighttime Pi2/Pc3 waves at low latitudes are produced by transmission of compressional mode to the ground. Observed amplitude-phase relationships are consistent with predictions of the thin ionosphere model.